The Role of A20 in Cancer: Friend or Foe? - Jinju Lee; Heesun Cheong (Cells)
A20 is a ubiquitin-editing enzyme that has emerged as a key regulator of inflammatory signaling with paradoxical roles in cancer. Acting as both an oncogene and a tumor suppressor gene depending on the cellular context, A20 modulates important cell pathways, such as NF-κB signaling and autophagy. In this review, we summarize the dual roles of A20 in tumorigenesis, highlighting its ability to promote tumor progression in cancers, such as breast and melanoma, while functioning as a tumor suppressor in lymphomas and hepatocellular carcinoma. We discuss the interplay of A20 with autophagy, a process that is important for maintaining cellular homeostasis and influencing tumor dynamics. By integrating recent findings, we provide insight into how dysregulation of A20 and its associated pathways can either suppress or drive cancer development, which may lead to improved therapeutic intervention.